Methotrexate delayed wound healing of a pyogenic granuloma in a child with juvenile idiopathic arthritis. - Schwarzmeier, Lígia Ângelo Tavares; Kitakawa, Dárcio; Rosa, Luiz Eduardo Blumer; Cabral, Luiz Antonio Guimarães; Almeida, Janete Dias (Brazilian Dental Science, 2019)
A nine-year-old girl with of juvenile idiopathic arthritis (JIA) in use of methotrexate complained of a self-bleeding ulcerated lesion exhibiting a red surface in the lower lip. Pyogenic granuloma was confirmed by histopathological analysis. After the 7th and 15th days, the lip where biopsy had been done exhibited a deficient healing. The case was discussed with the physician for temporary suspension of methotrexate. Complete wound healing of the biopsied site occurred after temporary interruption of the medication. Wound healing after methotrexate temporary suspension allowed concluding that the drug delayed surgical wound healing was a consequence of drug cytotoxicity.